Microstructure and microhardness of nickel-base heat-resistant alloys obtained by directional and equilibrium crystallization - Trostianchyn Andriy; Shvachko Serhii; Kulyk Volodymyr; Pleshakov Eduard; Molkov Yuriy; Lenkovskiy Taras (Lviv Politechnic Publishing House, 2019)
In order to determine the safe operational life of the components of gas turbine engines (GTE), introductory tests of nickel-base heat-resistant alloys (NHRA) have been performed. X-ray fluorescence and X-ray diffraction analyzes, optical microscopy and Vickers hardness measurements provided data on the phase-structural state and mechanical properties of the pristine ZhS6K-VI and ZhS32-VI alloys obtained by equilibrium and high-speed directional crystallization, respectively. Almost complete compliance of the investigated materials with the certified alloys in chemical and phase composition has been found. A significant difference in the parameters of the fragments of the microstructure of the investigated alloys, which is naturally consistent with the conditions of equilibrium and high-speed directional crystallizations, was revealed. A slightly lower anisotropy of microhardness (2.8 %), measured in transverse and longitudinal sections, was found in the ZhS6K-VI alloy as compared to the anisotropy (5.1 %) in the ZhS32-VI alloy. The obtained results will be used to test a nondestructive method for determining the safe operational life of gas turbine engine components.
Keywords: heat-resistant alloys, nickel-base superalloys, directional crystallization, equilibrium crystallization, gas turbine, blade, microstructure, microhardness